Associations between social norms and at-risk status for e-cigarette use: A sex-stratified analysis of Texas sixth-grade students - Sarina A. Attri; Andrew E. Springer; Baojiang Chen; Steven H. Kelder; Dale S. Mantey (Drug and Alcohol Dependence Reports)
Background: E-cigarette use remains high among adolescents, underscoring the need to identify targetable risk factors for intervention. This study examines associations between two social norms constructs (prevalence misperceptions and social acceptability) and at-risk status for e-cigarette use among Texas early adolescents. Methods: We conducted a cross-sectional analysis of baseline data from the CATCH My Breath study, which included n=1032 Texas sixth graders. Students who had ever used or were susceptible to using e-cigarettes were categorized as at-risk for long-term use. Susceptibility was measured using a 3-item index assessing curiosity, intentions, and receptivity to using e-cigarettes. Multi-level logistic regressions assessed associations between social norm constructs and at-risk status for the full and sex-stratified samples. Covariates were race, ethnicity, academics, household/peer tobacco use. Results: Overall, 36 % of 6th grade students were at-risk for e-cigarette use. Approximately 49 % of students overestimated peer e-cigarette use (“prevalence misperceptions”), and 43 % believed adolescent e-cigarette use is highly acceptable (“social acceptability”). Controlling for covariates, students with medium (aOR=1.89; 95 %CI=1.35–2.65) and high (aOR=1.98; 95 %CI=1.41–2.78) prevalence misperceptions had greater odds of being at-risk for e-cigarette use than those with low misperceptions. Students reporting medium (aOR=2.50; 95 %CI=1.66–3.76) and high (aOR=4.70; 95 %CI=3.21–6.90) social acceptability had greater odds of being at-risk for e-cigarette use than those reporting low acceptability. This association was stronger for females, relative to males. Conclusions: Greater prevalence misperceptions and social acceptability were associated with being at-risk for e-cigarette use among this sample of Texas early adolescents. Interventions should consider incorporating these social norms into intervention content.